Find the values of k for which the equation (2k-3)x^2 - kx + (k-1) = 0

A quadratic equation has two equal roots when its discriminant is equal to 0. Calculating the discriminant of the given equation: D = k2 - 4(k-1)(2k-3) = k2 - 8k2+20k-12 = -7k2+20k-12=0 Solving this equation for k: 7k2-20k+12=0 D = 100-84 = 16 k1,2=(10+-4)/7 => k = 6/7, k=2

Answered by Katerina P. Maths tutor

4100 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Edexcel January 2007 - Question 4 (Rates and Differential Equations)


Find the derivative (dy/dx) of the curve equation x^2 -y^2 +y = 1.


The curve C has the equation y = 2x^2 -11x + 13. Find the equation of the tangent to C at the point P (2, -1).


Use the substitution u=4x-1 to find the exact value of 1/4<int<1/2 ((5-2x)(4x-1)^1/3)dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences